Cyprus Association of Graphic Designers and Illustrators (CAGDI) - (:unkn) unknown (My University, 2026)
The Association* (Association, for reference reasons) is the official association of graphic designers and illustrators of Cyprus who are either employed by companies and organizations or work as self-employed or are teachers in the field of graphics and/or illustrations.